Pengembangan Media Pembelajaran Matematika dengan Bantuan Canva pada Materi Peluang - Fauzia, Nur (Department of Mathematics Education, Faculty of Tarbiyah, Institut Agama Islam Negeri Parepare, 2024)
The aim of this research is to describe the process and find out the results of the development of Canva-assisted mathematics learning media for class VIII opportunity material at SMP Negeri 4 Enrekang and to find out whether the media can help students understand opportunity material. This type of research is research and development using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model developed by Robert Maribe Branch. This product trial was carried out on 28 students in class VIII B at SMP Negeri 4 Enrekang. The ADDIE model in Analysis, researchers analyzed the curriculum, materials, needs and characteristics of students. Then in Design, the template design and animation are carried out. Meanwhile, in Development, media creation, media revision and media assessment are carried out. These results show that the level of validity based on expert validation is at the